2021
DOI: 10.1136/jitc-2021-002671
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation-based signature of CD8+ tumor-infiltrating lymphocytes enables evaluation of immune response and prognosis in colorectal cancer

Abstract: BackgroundTumor-infiltrating lymphocytes (TILs), especially CD8+ TILs, can be used for predicting immunotherapy responsiveness and survival outcome. However, the evaluation of CD8+ TILs currently relies on histopathological methodology with high variability. We therefore aimed to develop a DNA methylation signature for CD8+ TILs (CD8+ MeTIL) that could evaluate immune response and prognosis in colorectal cancer (CRC).MethodsA CD8+ MeTIL signature score was constructed by using CD8+ T cell-specific differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…Thus, not only will most patients with this subset NTRK+ CRC benefit from the current approved NTRK TKIs, but may also potentially benefit from ICIs. Notably, a prior study by Zou et al 20 reported that enriched CD8+ tumor‐infiltration T cells, quantified by using a DNA methylation‐based method, was associated with MSI‐H tumors in CRC cohorts and predicted better survival. However, it will require further investigation as to whether two molecular signatures (TMB and MSI) being positive, the response to pembrolizumab will be higher (additive or synergistic effect) than just having one molecular signature.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, not only will most patients with this subset NTRK+ CRC benefit from the current approved NTRK TKIs, but may also potentially benefit from ICIs. Notably, a prior study by Zou et al 20 reported that enriched CD8+ tumor‐infiltration T cells, quantified by using a DNA methylation‐based method, was associated with MSI‐H tumors in CRC cohorts and predicted better survival. However, it will require further investigation as to whether two molecular signatures (TMB and MSI) being positive, the response to pembrolizumab will be higher (additive or synergistic effect) than just having one molecular signature.…”
Section: Discussionmentioning
confidence: 99%
“…Among the ESTIMATE scores of the four ImmClusts, the highest immune ( Figure 2A ) and stromal scores ( Figure 2B ) were observed in CS2, in contrast to the lowest scores in CS4 ( Figures 2A, B ) . A study has shown that the MeTIL score system may assess immune and immunotherapy responses in CRC ( 54 ). Interestingly, our data suggested that CS2 had the highest MeTIL score ( Figure 2C ), while CS4 had the lowest MeTIL score, which further suggested the differences in immunotherapy responses among the four ImmClusts.…”
Section: Resultsmentioning
confidence: 99%
“…The five markers comprise single CpG sites of five individual genes, including INA , KLHL6 , PTPRCAP , RASSF1 , and SEMA3B , which are different from the three methylation markers in the present study 10 . During the submission of our manuscript, it was reported that Zou et al developed DNA methylation signature for CD8+ TILs that could assess CD8+ TILs in colorectal cancers, using three individual CpG sites that are located in the low-CpG density regions and highly differentially methylated between CD8+ T cells and other cells 20 . The selected CpG sites are not located within CpG island loci, so that classical MethyLight assay could not assess methylation levels of these single CpG sites.…”
Section: Discussionmentioning
confidence: 99%